Pelatihan dan Pendampingan Pembuatan Ale Toraja Untuk Peningkatan Kreativitas Anak di Panti Asuhan Kristen Tangmentoe - Siska Appa; Desi Ratna Sari; Krisnawati Todingallo; Hizkia Patadungan; Vonnisye; Berlian Zetikarya Haryati (Wahana Dedikasi: Jurnal PkM Ilmu Kependidikan, 2023)
The primary issues with this activity are the kids' lack of imagination and ignorance of Toraja wisdom from the Tangmentoe Christian Orphanage. The purpose of conducting this community service activity is to enhance the creativity of the orphanage children through training and mentoring in making Toraja Ale. The community service projects were conducted at the Tangmentoe Christian Orphanage in August through October 2023. Three components make up the activity's implementation techniques: mentorship in weaving skills, training, and counseling. Assessment exercises were also conducted to gauge the orphanage children's progress in terms of their knowledge, abilities, and inventiveness. The outcomes of the community service projects demonstrated a rise in understanding of Toraja folk wisdom. Following the post-test, the average score increased from 20 to 85. In addition, the orphanage children's skills increased from 5% to 80%, and their creativity increased from 80% being non-creative to 10% being highly creative, 60% being creative, 20% being somewhat creative, and 10% not creative.